Being the Family Caregiver of a Patient With Dementia During the Coronavirus Disease 2019 Lockdown - Zucca, Milena; Isella, Valeria; Lorenzo, Raffaele Di; Marra, Camillo; Cagnin, Annachiara; Cupidi, Chiara; Bonanni, Laura; Laganà, Valentina; Rubino, Elisa; Vanacore, Nicola; Agosta, Federica; Caffarra, Paolo; et al. (Frontiers in Aging Neuroscience, 2021)
Background: Family caregivers of patients with dementia are at high risk of stress and burden and quarantine due to COVID-19 pandemic may have increased the risk of psychological disturbances in this population. The current study was carried out during the national lockdown declared in March 2020 by the Italian government as a containment measure of the first wave of coronavirus pandemic, and is the first nation-wide survey on impact of COVID-19 lockdown on mental health of dementia informal caregivers. Methods: Eighty-seven Dementia Centers evenly distributed on the Italian territory enrolled 4710 caregiver-patient pairs. Caregivers were delivered a telephone interview assessing classical symptoms of caregiver stress and concern for the consequences of COVID-19 infection on patient’s health. We calculated prevalence of symptoms and regressed them on various potential stress risk factors: caregivers' socio-demographic characteristics and lifestyle, patients' clinical features, and lockdown-related elements, like discontinuity in medical care. Results: Approximately 90% of caregivers reported at least one symptom of stress, and nearly 30% reported four or more symptoms. The most prevalent symptoms were Concern for consequences of COVID-19 on patient's health (75%) and Anxiety (46%). The main risk factors for stress were identified as a conflicting relationship with the patient and discontinuity in assistance, but caregiver's female sex, younger age, lower education and cohabitation with the patient also had an impact. Availability of help from institutions or private individuals showed a protective effect against Sense of Abandonment, but a detrimental effect on concern about the risk for the patient to contract COVID-19. The only protective factor was mild dementia severity, which was associated with a lower risk of feeling isolated and abandoned; type of dementia, on the other hand, did not affect stress risk. Conclusion: Our results demonstrate the large prevalence of stress in family caregivers of patients with dementia during COVID-19 pandemic, and has identified both caregivers and situations at higher risk of stress, that should be taken into account in the planning of interventions in support of quarantined families and patients.